Measurement in Machining and Tribology - Davim, J. Paulo (Materials Forming, Machining and Tribology,, 2019)
This book presents the research advances in the science of measurement, giving special focus to the field of machining and tribology. Topics such as dimensional metrology, precision measurements, industrial metrology, accuracy and precision in measurement are covered. Also theoretical aspects such as modelling and simulation are highlighted.